Lex actualization on describing of military acts, processes and states - Maryna Navalna; Yuliia Kaluzhynska (Психолінгвістика, 2018)
The article describes the most commonly used lexemes from the texts of contemporary Ukrainian periodicals, reveals new lexicalunits, expands thes copeof the operation oflexemasonmilitarytopicsinthemediamaterialsofsocio-political, military an do the rissues; thefunctional-stylistic role of military vocabulary in the language of the pressis determine dandemphasizedon a negative evaluation injournalistic materials.